Daily Behavior of Javan Bull (Bos javanicus javanicus) in Ragunan Wildlife Park - Afghan Nail Irfan; Indri Yani; Awaludin, Muhammad Taufik (Journal Of Biology Education Research (JBER), 2025)
Indonesia has quite a variety of endemic animals. One of Indonesia's endemic animals is the Javan bull (Bos javanicus javanicus). This animal comes from the island of Java and is now a protected animal. The decline in the Javan bull population in Indonesia is caused by illegal hunting, habitat destruction and exploitation. Conservation efforts are needed to protect and preserve the Javan bull. There is ex-situ conservation as a place to preserve various types of animals with a modern concept. Ragunan Wildlife Park is an ex-situ conservation area created in a way that matches its natural habitat. The aim of this research is to describe the daily behavior of Javan bulls and differences in the percentage of behavior of each individual Javan bull (Bos javanicus javanicus) in the Ragunan Wildlife Park ex-situ captivity. This research was carried out with a total of 12 days of observation on 4 Javan bulls, namely 2 males and 2 females. Observations were divided into 2 sessions. The morning session was held at 08.00-11.00 WIB and the afternoon session was held at 13.00-15.00 WIB using the focal animal sampling method. The parameters measured are temperature and humidity. Based on the results of research that has been carried out, the behaviors of Javan bulls that emerge are eating, drinking, ruminating, moving, resting, sleeping, grooming, urinating, defecating and social behavior. The highest behavior of the Javan bull (Bejo) was social behavior at 32.56% and the lowest was defecation behavior at 0.44%. The dominant behavior of Javan bulls (Raju) is resting behavior at 39.56% and the lowest is urination behavior at 0.22%. The highest behavior of the Javan bull (Amy) was eating behavior at 35.00% and the lowest was drinking and defecation behavior at 0.33%. The highest behavior of the Javan bull (Susi) was eating behavior at 49.44% and the lowest was sleeping behavior at 0.00%.